BUSINESS STRATEGY FORMULATION OF INDIHOME PT. TELEKOMUNIKASI INDONESIA AREA OF WEST NUSA TENGGARA - Mia Ananda Fatimah; H.A., Romadlon; Risris Rismayani (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2020)
This study aims to determine the priority strategies of several alternative strategies in IndiHome which are formulated using SWOT analysis. This research is a qualitative descriptive study. The data used are primary. Sampling using a purposive sampling technique and get seven informants. Primary data generated from the interviews were analyzed using SAP and ETOP to diagnose factors including strengths, weaknesses, opportunities, and threats. After that, these factors are formulated in the SWOT matrix to determine alternative strategies. Strategy alternatives are then formulated in the QSPM matrix to obtain priority strategy results for IndiHome. The validity test in this study was carried out by triangulation of sources. The results showed that there were four alternative strategies for IndiHome Telkom Area of West Nusa Tenggara. Based on four alternative strategies, the priority strategy for IndiHome which is determined by QSPM matrix is to upgrade the quality of services provided to customers regularly with a total weight of 7,051. The results of this study are expected to be able to assist in the framework of thinking about strategic management knowledge in the Internet Service Provider (ISP) industry and also provide additional information and insights in the selection of alternative strategies as well as new insights about the condition of the company from an external perspective.